A systematic review of OCT and OCT angiography in retinal vasculitis - Dhirachaikulpanich D. (2023)
Background: Retinal vasculitis is a component of uveitis for which the Standardisation of Uveitis Nomenclature (SUN) working group has no standard diagnostic criteria or severity grading. Fluorescein angiography is the gold standard test to assess retinal vasculitis, but is invasive and time-consuming. Optical coherence tomography (OCT) provides non-invasive detailed imaging of retinal structures and abnormalities, including blood vessel architecture and flow with OCT angiography (OCT-A). However, use of OCT in retinal vasculitis beyond assessing macular oedema, is not well established. We conducted a systematic review to understand the features of retinal vasculitis in OCT, Enhanced-depth imaging OCT (OCT-EDI) and OCT-A imaging. Methods: The systematic search was done in March 2022 and updated in January 2023, through PubMed, EMBASE and the Web of Science database for studies related to OCT, OCT-EDI and OCT-A findings and retinal vasculitis. Bias assessment was assessed using JBI Critical Appraisal Checklist, and any findings associated with retinal vasculitis were extracted by qualitative analysis. Results: We identified 20 studies, including 8 articles on OCT, 6 on OCT-EDI and 6 on OCT-A. The studies included analytical retrospective studies, case-series, and a case–control study. Five OCT studies reported secondary complications could be detected, and four reported retinal thickness alteration in retinal vasculitis. Five studies explored choroidal thickness alteration in OCT-EDI, and four explored capillary density alterations in retinal vasculitis using OCT-A. The heterogeneity in the studies’ analysis and design precluded a meta-analysis. Discussion: There were no clear OCT, OCT-EDI or OCT-A findings that demonstrated potential to supersede fluorescein angiography for assessing retinal vasculitis. Some signs of macular structural effects secondary to retinal vasculitis may help prognostication for vision. The OCT signs of inflamed retinal vessels and perivascular tissue is an unexplored area.